PSYCHOSOCIAL DEVELOPMENT OF THE CHILDREN - Riendravi, Scania (E-Jurnal Medika Udayana; vol 2 no 11 (2013):e-jurnal medika udayana)
Normal 0 false false false EN-US X-NONE X-NONE Family have an important role as a basic of emotional and social development. Friendships also influence the psychosocial development of the children. Psychosocial development of children will be improved with changes in their knowledge and understanding of the needs and regulations. Understand the psychosocial development of the children will help the parents and teachers educate their childrens / students and optimize the process of development in a proper way. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: psychosocial development of the children, role of the family, friendship